Pesticides in Agriculture and Environment - Kassio Ferreira Mendes (Pesticides in Agriculture and Environment, 2021)
Pesticides applied worldwide in conventional agriculture for pest, disease and weed control are critical to increased productivity, but can provide harmful effects on non-target organisms. Given its toxicological, environmental and agricultural relevance, pesticide science comprises an important area of research, not only for scientists working in the field of agriculture, but also for several other professionals, where the subject requires a multidisciplinary approach. Important aspects of pesticides residues in marketed grains in Brazil, contamination of water resources by pesticides, bioaccumulation of pesticides in non-target organisms, are highlighted in this book, in addition to advantages and disadvantages of hormesis to herbicides in agricultural production, and phytoremediation technique to herbicides-polluted soils. We are sure that readers will find a lot of useful information, even if they are only partially interested in a few chapters. In this book entitled "Pesticides in Agriculture and Environment" are covered several topics on current and valuable research on pesticide science.